La búsqueda del prototipo: reflexiones sobre los parámetros de categorización - Martos Ramos, José Javier (Revista de Filología Alemana, 2010)
As Rosch and Kleiber conceive them, this article takes for granted that prototypes contain several features that support communication and understanding among speakers. Thanks to the communicative mechanisms involved and the poor cognitive effort needed a great quantity of information is transmitted. This article analyses and proposes several factors and parameters which help to organize and systematize the categorization process in language such as frequency, accumulation, distance, commutability, representativity or to be the first in naming. This theoretical approach has been used in several studies on German.